2021
DOI: 10.1016/j.ejpn.2021.03.014
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the early motor repertoire of very preterm infants and term infants

Abstract: Objective: To obtain reference data on the early motor repertoire of very preterm infants compared with healthy term infants at three months' post-term age. Study design: In this observational study, using Prechtl's method on the assessment of the early motor repertoire, we compared the quality of fidgety movements and the concurrent motor optimality scorerevised of infants with a gestational age <30 weeks and/or a birth weight <1000 g with healthy infants with a gestational age of 37e42 weeks. Results: One hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 28 publications
1
23
0
Order By: Relevance
“…In our study, in both groups, the most common score was in the "mildly reduced" range, which means a score between 20 and 24, most likely due to prematurity. This corresponds to the results of Salavati et al, 2021. In this study 180 very preterm and 180 healthy term infants participated.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…In our study, in both groups, the most common score was in the "mildly reduced" range, which means a score between 20 and 24, most likely due to prematurity. This corresponds to the results of Salavati et al, 2021. In this study 180 very preterm and 180 healthy term infants participated.…”
Section: Discussionsupporting
confidence: 84%
“…These include BPD, sepsis, and hypoglycemia each of which may lead to impaired neurodevelopment and cognition (57)(58)(59). As discussed above, preterm birth is itself a risk for worse outcome in the MOS-R (47). Another limitation is partly incomplete existence of videos due to the following: Video analysis of motor function at 3 months of age was only gradually introduced in follow-up care from 2017.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 Existing prospective cohort studies of very low birthweight infants have found that higher motor optimality scores are associated with better motor function at 1 year 17 and with cognitive, language and motor development of very preterm infants at 2 years. 18 Recent studies have identified median MOS-R between 24 and 26 for infants born at term, [19][20][21][22][23] and a study investigating the difference in infants born EP with adverse outcomes found lower median MOS-R (17.5) compared with infants born EP with a normal outcome (median MOS- R 21). 24 To our knowledge, no studies have documented typical MOS-R scored from…”
Section: While Fidgety Movements Have Good Predictive Validitymentioning
confidence: 99%
“…A method to reliably assess early neurological functioning is by assessing the early motor repertoire of infants. At 9–16 weeks post-term, the early motor repertoire includes fidgety movements (FMs), small circular movements visible in all joints ( 13 ), as well as several other movement and postural patterns, which together form the basis for the motor optimality score – revised (MOS-R) ( 14 ). The early motor repertoire, including the MOS-R, is reported to be predictive of cerebral palsy (CP).…”
Section: Introductionmentioning
confidence: 99%